An investigation of enhancement of ability evaluation by using a nested logit model for multiple-choice items - Liu, Tour; Wang, Mengcheng; Xin, Tao (Anales de Psicología / Annals of Psychology, 2017)
Multiple-choice item is wildly used in psychological and educational test. The present study investigated that if a multiple-choice item have an advantage than a dichotomous item on ability evaluation.An item response model,nested logitmodel (NLM),was used to fit the multiple-choice data. Both simulation study and empirical study indicated that the accuracy and the stability of ability estimation were enhanced by using multiple-choice model rather than dichotomous model, because more information was included in multiple-choice items’ distractors. But the accuracy of ability parameter estimation showed little differences in 4-choice items, 5-choice items and 6-choice items. Moreover, NLM could extract more information from low-level respondents than from high-level ones, because they hadmore distractor chosen behaviors. Furthermore, respondents at different trait levels would be attracted by different distractors in an empirical study of a Chinese Vocabulary Test for Grade 1 by using the changing traces of distractor probabilities calculated from NLM. It is suggested that the responses of students at different levelsmight reflect the students’ vocabulary development process.